The importance of oral hygiene in reducing the incidence of ventilator-associated pneumonia : a systematic review - Buković, Ema (Array, 2019)
Introduction. Healthcare-associated infections (HCAIs) represent a major public health problem. Inadequate oral hygiene in intensive care units has been recognized as a critical issue for the occurrence of one of these infections – ventilator-associated pneumonia (VAP). Although literature suggests diverse oral care measures for ICU patients, the effectiveness of each is still a subject for further trials. Aim. The purpose of this paper is to determine the association between diverse oral care measures and the incidence of ventilator associated pneumonia. Methods. A systematic review of literature in the PubMed database that evaluates the performance of diverse oral care measures and their impact in reducing the incidence of VAP. The keywords used as search terms were: oral hygiene, ventilator-associated pneumonia, intensive care unit and nursing. Results. Four articles in total were taken into consideration in accordance with the availability of full-text articles and years of publication between 2009 and 2019. Performance results of diverse oral care measures haven’t shown statistically significant differences, but the implementation of oral care as a preventive measure against VAP showed a significant role in lower incidence rates. Conclusion. The results of the systematic literature review confirmed the importance of oral care in lowering the incidence rate of VAP. However, significant differences have been noted between the efficiency of diverse oral care measures and the incidence rate of VAP.